English Public Speaking Anxiety of Third-Year Students from a Tertiary Education Institution - Asio, John Mark; Caingal, Criscel Anne; Alla , Ericka Rei; Bulan, Whendell Jan; Marcial, Madeleine (PT FORMOSA CENDEKIA GLOBAL, 2024)
The present study investigates the English public speaking anxiety of the third-year students from a tertiary education institution in Olongapo City, Philippines. One hundred ninety-seven (197) purposively selected respondents participated in the exploration of the four main components of English Public Speaking Anxiety. The researchers then analyzed the collected data through nonparametric tests. Results yielded no significant difference in the level of public speaking anxiety of the third-year students however when grouped by sex and program, the study found significant findings. With this, researchers proposed a seminar-workshop to help student-respondents increase their self-esteem and confidence in using English as their medium in facilitating their future students.